Accounting and Auditing at the Time of Blockchain Technology: A Research Agenda. Issue 2 (4th April 2019) - Schmitz, Jana; Leoni, Giulia
Abstract: Blockchain is a distributed ledger technology expected to have significant impacts on the accounting and auditing profession. This study, applicable and timely for both accounting and auditing scholars and practitioners, explores blockchain technology and its main implications for the accounting and auditing profession. The research question addressed in this study is: What are the major themes emerging from academic research and professional reports and websites debating blockchain technology in the accounting and auditing context? A literature review of academic literature and professional reports and websites is performed to identify a taxonomy of emerging themes. The study finds that the most discussed themes in scholarly works and professional sources are governance, transparency and trust issues in the blockchain ecosystem, blockchain‐enabled continuous audits, smart contract applications and the paradigmatic shift in accountants' and auditors' roles . Based on these four themes, practical implications for accountants and auditors on how to approach the blockchain development are provided. Moreover, this study offers suggestions for future research on accounting and auditing in the blockchain era. Abstract : This study identifies four major themes that emerge from the current debate on blockchain technology in the accounting and auditing sphere. These findings do not only translate into implications for accountants and auditors on how to approach blockchain technology but also provide a roadmap outlining potential research avenues.